Peran Guru Pendidikan Agama Islam (PAI) dalam Penguatan Gender di Sekolah - Arum Rizqi Aprilia; Nurul Arifah Shofiana; Nurul Mubin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Education is a conscious effort to change one's life. Everyone in this world, men and women have the same right to learn. However, not everyone agrees with this statement. Gender equality is one of the problems in seeking knowledge. Many still think that women do not need to be highly educated. Because in the end women will become housewives. Many men think that housework is only for women. This is carried over to the school environment, for example, most boys do not want to do class duty. They think that duty is a woman's job. With this way of thinking, gender equality in duty is still not balanced between men and women. Efforts that can be implemented by Islamic Religious Education teachers to strengthen gender equality include providing advice, providing motivation, habituation training and providing guidance. This can be done in between materials during learning.